Action of new epimutagen factor on winter wheat at cytogenetic level - Okselenko, Oleh; Окселенко, Олег Миколайович; Nazarenko, Mykola; Назаренко, Микола Миколайович; Horshchar, Vladyslav; Горщар, Владислав Іванович (Дніпровський національний університет імені Олеся Гончара, 2025)
This study evaluated the epimutagenic potential of Nonidet P-40 (NP-40) in winter wheat by examining its ability to induce chromosomal aberrations, elucidating genotype-mutagen interactions, and assessing its predictive value at the cellular level for inducing epigenetic mutations at the plant level. Four winter wheat (Triticum aestivum L.) varieties – Perspektyva Odeska, Sonata Poltavska, Shpalivka, and MIP Lada – were treated with NP-40 at concentrations of 0.01%, 0.05%, 0.1%, and 0.5%. Cytogenetic effects were evaluated through pollen sterility and the frequency and spectrum of chromosomal aberrations during mitosis in root-tip cells. Results demonstrated significant genotype-specific responses to NP-40 treatment, particularly highlighting the variety MIP Lada as highly responsive. This variety showed the greatest genotype-specific sensitivity, making it a strong candidate for targeted induction of genetic variability and selection of mutant forms. Among tested concentrations, 0.5% NP-40 proved most effective, inducing substantial chromosomal aberrations while maintaining acceptable viability, thus optimizing mutation induction and limiting adverse effects. Conversely, moderate NP-40 concentrations (0.01–0.10%) were less effective, striking an inadequate balance between beneficial mutation induction and viability. Key cytogenetic indicators of genotype susceptibility included pollen fertility rates, overall chromosomal aberration frequencies, and the incidence of rare cytological anomalies such as micronuclei and lagging chromosomes. In contrast, the abundance of fragments and bridges was less analytically informative. Notably, the chromosomal aberration induction patterns by NP-40 were distinct from those observed previously with classical chemical supermutagens, varying significantly according to genetic background. These findings provide critical insights into the epimutagenic properties of NP-40, emphasizing the importance of genotype selection and concentration optimization for effective breeding strategies. Further research will integrate these cytogenetic findings with studies on hereditary variability in biochemical and physiological traits, thereby refining epimutagenic strategies and optimizing breeding programs for winter wheat improvement. У цьому дослідженні оцінили епімутагенний потенціал Нонідету П-40 (NP-40) на озимій пшениці, досліджуючи його здатність індукувати хромосомні аберації, з'ясовуючи взаємодію генотип-мутаген та оцінюючи його прогностичну цінність на клітинному рівні для індукції епігенетичних мутацій на рівні рослин. Чотири сорти озимої пшениці (Triticum aestivum L.) – Перспектива Одеська, Соната Полтавська, Шпалівка та МІП Лада – були оброблені NP-40 у концентраціях 0,01%, 0,05%, 0,1% та 0,5%. Цитогенетичні ефекти оцінювали за стерильністю пилку та частотою й спектром хромосомних аберацій під час мітозу в клітинах кінчика кореня. Результати продемонстрували значну генотип-специфічну відповідь на обробку NP-40, особливо виділяючи сорт МІП Лада як високочутливий. Цей сорт показав найбільшу генотип-специфічну чутливість, що робить його сильним кандидатом для цілеспрямованої індукції генетичної мінливості та відбору мутантних форм. Серед протестованих концентрацій 0,5% NP-40 виявився найефективнішим, індукуючи суттєві хромосомні аберації, зберігаючи при цьому прийнятну життєздатність, оптимізуючи таким чином індукцію мутацій та обмежуючи побічні ефекти. І навпаки, помірні концентрації NP-40 (0,01–0,10%) були менш ефективними, порушуючи адекватний баланс між корисною індукцією мутацій та життєздатністю. Ключовими цитогенетичними показниками сприйнятливості генотипу були коефіцієнти фертильності пилку, загальна частота хромосомних аберацій та частота рідкісних цитологічних аномалій, таких як мікроядра та відстаючі хромосоми. Навпаки, велика кількість фрагментів та містків була менш аналітично інформативною. Примітно, що моделі індукції хромосомних аберацій за допомогою NP-40 відрізнялися від тих, що спостерігалися раніше з класичними хімічними супермутагенами, значно варіюючись залежно від генетичного фону. Ці результати дають критичне розуміння епімутагенних властивостей NP-40, підкреслюючи важливість відбору генотипу та оптимізації концентрації для ефективних стратегій селекції. Подальші дослідження інтегруватимуть ці цитогенетичні дані з дослідженнями спадкової мінливості біохімічних та фізіологічних ознак, тим самим удосконалюючи епімутагенні стратегії та оптимізуючи програми селекції для покращення озимої пшениці.
Дія нового епімутагенного фактора на озиму пшеницю на цитогенетичному рівні
Keywords: winter wheat; озима пшениця; chromosomal abberations; хромосомні аберації; Nonidet P-40; Nonidet P-40; genotype; генотип; cells; клітини; site-specific action; сайт-специфічна дія; chemical epimutagen; хімічний мутаген